The role of oxidative stress in rheumatic diseases - Özgöçmen, Salih (My University, 2007)
Reactive oxygen species and free radicals play important roles in physiologic and pathologic processes in the body. Data on the role of oxidative stress in the pathophysiology of inflammatory cascade and rheumatic diseases continues to accumulate. In this mini review oxidative stress mechanisms and new advances in the role of oxidative stress in the pathophysiology of rheumatic diseases have been briefly summarized.
Romatizmal hastaliklarda oksidatif stresin rolü
Keywords: Free radicals; Oxidative stress; Rheumatic diseases